Community pharmacists' patient counselling in Tasmania towards patient-oriented care - Robles, Yolanda R.
Pharmaceutical care is the new philosophy and mission of the pharmacy profession which is responsive and relevant to the changing health care priorities and problems associated with drug use in the 1990s. It is expected that this patient-oriented practice will enhance the contribution of the profession to positive health outcomes. However, the adoption of this ideal practice has been observed to be more consistent at the institutional level, rather than at the community setting. Numerous factors inherent to the community setting, hindering its wider implementation, are implicated in the literature. Of the major activities performed under pharmaceutical care, pharmacists were found to perform poorly in roles requiring active interaction with patients, particularly patient counselling. It was revealed in several studies such as a recent North American review, that there had been no substantial improvement in the quantity and relative quality of pharmacists' patient communication during the past 25 years. This grim assessment of pharmacists' performance in patient counselling has become a paradox in view of the clinical orientation in pharmacy education, government support and other reinforcing features of the community practice setting in Western countries. While this concern has been repeatedly addressed by various sectors in the profession through practice and education interventions, the re-examination of current philosophical and methodological issues in pharmacy practice research has been recently advocated and the consideration of their alternatives suggested in order to ascertain the real issues confronting pharmacists' counselling practice. The main objectives of the present work are 1) to develop a research methodology which will help generate a better underestanding of the subjective and contextual aspects of community pharmacists' patient counselling; 2) to design a specific educational intervention and its workplace evaluation based on the findings of training needs assessment and contextual analysis and 3) to identify the factors which affect the application of learning to the workplace within the practice context of community pharmacists in Tasmania. Preceded by a review of the social aspects of drug therapy in health care and the current state of pharmacists' patient counselling, this work critically examine and evaluates paradigms, approaches and methods on the basis of their appropriateness and applicability to current issues affecting pharmacists' patient counselling. From this analysis, a research framework and its methodology were designed and used in conducting training needs assessment and situational analysis covering some general and specific aspects of patient counselling by community pharmacists in Tasmania, particularly the counselling of non-insulin dependent diabetes mellitus (NIDDM) patients. A combination of methods, mostly qualitative, were used to gather pertinent data from the perspectives and experiences of community pharmacists, NIDDM patients and key health professionals.
Guided by a system for developing continuing pharmacy education (CPE development system) designed by the author in a previous work, findings from these studies were subsequently utilized in the development, implementation and evaluation of a training program entitled "A Training Program in NIDDM Patient Counselling for Community Pharmacists." The program has both diabetes knowledge and counselling skill components, was multi-disciplinary in approach and employed various learning methods, including the microcounselling training method. Evaluation of this educational intervention, consisting of quantitative and qualitative methods, focused not only on the immediate educational outcomes but also on the workplace application of the training provided. The workplace evaluation, mainly in the form of case studies and aided by a NIDDM patient counselling kit, identified the specific factors affecting the integration of learned training components into the actual practice of, and elucidated the details of the contextual nuances ascribed to those factors by, individual pharmacists. In conclusion, the elucidation of personal and contextual factors affecting pharmacists' performance of patient counselling could be achieved by the use of qualitative methods chosen according to important theoretical, methodological and practical research considerations. Findings by qualitative research methods provide meaningful, detailed explanation of the factors previously identified through quantitative means. The educational intervention developed in this work, based on specifric needs assessmment, contextual analysis and other elements of the CPE development system, tends to enhance pharmacists' counselling performance, albeit, in highly individualized degrees and nature practice integration. It is recommended that 1) qualitative methods be used in research where detailed aspects of pharmacists' perspectives will be necessary to explain observed phenomena, 2) workplace evaluation and follow-up be considered as value-added components of CPE programs to identify individual and workplace factors which are actually experienced by pharmacists as affecting their application of learning in the community setting and that 3) group support systems in the profession be developed to help pharmacists, particularly owners and managers to address workplace barriers hindering their full assumption of role in patient-oriented care.
Available to the general public.
Thesis (Doctor of Philosophy in Pharmacy)--University of Tasmania, September 1998.
Keywords: Community Pharmacy Services; Patient education; Counseling